A comparative Study to Evaluate the Effect of Sodium hypochlorite Temperature on Cyclic Fatigue Resistance of Three Types of Rotary Instrument (Mustansiria Dental Journal, 2018)
Background: The fracture of instruments within root canal during endodontictreatment is a common incidence, fracture of fatigue through flexure occursbecause of metal fatigue, NaOCl used for irrigation may have an effect oncorrosion that decrease fracture resistance. This study aimed to assess the effect ofNaOCl temperature on the cyclic fatigue of different type of Endodontic NiTiRotary Instruments and compare among them.Materials and method: three types of rotary instruments with tip size 0.25: ProTaPerF2 (Densply,Malifier) Revo-S SU ( 0.06 taper, MicroMega) and RaCe system(0.06 taper, FKG,Dentaire), Thirty file of each instrument type were used withincanal with 60° angle of curvature , undiluted NaOCl (5.25% ) were used. Ten filewithout immersion in NaOCl, ten were immersed at room temperature (21°C) for5 minute and ten with immersion in NaOCl at 60°C for the same time. Nine groupwere formed for all instruments (total number=90). The testing canal customizedwithin stainless steel block covered with glass face, the time to fracture recordedand the mean of cycles to fracture (MCF) detected for each instrument .Data wereanalyzed statistically by ANOVA, LSD and Independent T-test at 5% significantlevel.Result: there was a highly significant difference in mean of cycles to fracture for eachrotary instrument when temperature of NaOCl increased that the Number of cyclesto fracture decreased as the temperature increased. RaCe revealed the best fractureresistance followed by ProTaper then Revo-s that showed the less resistance.Conclusion: the rotary instruments more prone to fracture when temperature ofNaOCl increased, as well as the rotary instruments differ from each otheraccording to manufacturing process, taper, cross section and other factors.